Abs composite resin for improving gloss of product and preparation method thereof

CN122941133APending Publication Date: 2026-10-20高丛富
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411010792.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0035]1、本发明通过使用异戊二烯,丁二烯与苯乙烯,丙烯腈制得共聚物,通过本体法ABS与共聚物复配使用,加入抗老化剂,增韧剂,阻燃剂,抗氧剂制得ABS复合树脂;通过改变注塑温度以及注塑压力,提高复合树脂的光泽度。由于在合理的橡胶相粒径范围内,随着橡胶粒径的增大,对光的散射作用减弱,树脂的光泽性下降,通过调整异戊二烯以及丁二烯的用量比,改变共聚物的粒径大小,制得的ABS复合树脂的光泽度为96.2%,具有明显提高的光泽度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of resin material preparation technology, specifically to an ABS composite resin for improving product gloss and its preparation method. The ABS composite resin is prepared by high-speed uniform mixing of bulk ABS, copolymers, toughening agents, anti-aging agents, and flame retardants, followed by melt blending and extrusion in a twin-screw extruder, and injection molding. This invention achieves high gloss in the composite resin by controlling the isoprene to butadiene ratio and adjusting the emulsion particle size; improves the tensile strength of the composite resin by changing the type and amount of ABS used in the bulk process; improves the impact strength of the composite resin by controlling the type and amount of toughening agent; improves the aging resistance of the composite resin by using an anti-aging agent prepared by modifying nano-titanium dioxide with fluorosilane; and improves the flame retardant performance of the composite resin by using a flame retardant prepared by compounding a benzoxazine flame retardant with triphenyl phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of resin material preparation technology, specifically to an ABS composite resin for improving product gloss and its preparation method. Background Technology

[0002] ABS resin plastic is the most produced and widely used polymer today. It has good physical and mechanical properties, high impact strength, good chemical stability and electrical properties, good processing and machining performance, and is resistant to water, inorganic salts, acids and alkalis, making it a widely applicable engineering material. However, current ABS resin plastics still have disadvantages such as low strength, poor surface abrasion resistance, weak flame retardancy and heat resistance under extreme conditions, and poor surface gloss.

[0003] ABS resin generally uses linear rubber as a toughening agent. However, linear rubber cannot simultaneously achieve high gloss and high impact strength, often exhibiting defects such as low mechanical strength and poor gloss. It is also susceptible to the effects of factors such as ultraviolet radiation, oxygen, humidity, and temperature. Ultraviolet radiation can trigger free radical reactions in ABS resin materials, and subsequent oxygen will further oxidize the ABS resin molecular chains, causing damage to the molecular chains. This will significantly reduce the strength and toughness of ABS plastic, thus causing ABS resin to age easily and reducing the service life of ABS resin materials.

[0004] In addition, ABS resin has a limiting oxygen index of only 18.3-20%, making it a flammable polymer material. When used in various electronic and electrical products with flame retardant requirements, flame retardant modification is required to meet the safety and fire protection requirements. Currently, the most mature and effective flame retardant modification method for ABS is to add bromine-based flame retardants and antimony-based flame retardants. However, the addition of flame retardants affects the weather resistance of the material and can easily lead to premature aging of important components such as battery casings, thereby shortening the service life.

[0005] Patent CN201410181195.4 reports a halogen-free flame-retardant and heat-resistant ABS plastic for automotive interior parts and its preparation method. The ABS plastic includes ABS resin and PVC resin, and the flame-retardant effect of the plastic is improved by adding flame retardants and heat resistant agents. It has the advantages of low production cost and good processing performance. However, in actual use, the addition of flame retardants causes a decrease in the weather resistance of the material, and the flame-retardant performance needs to be further improved.

[0006] Patent CN201610964668.7 discloses a high-filler, high-impact, and high-weather-resistant PC-ABS composite material and its preparation method. The ABS composite material is prepared by adding polycarbonate, acrylonitrile-butadiene-styrene graft copolymer, compatibilizer, filler, toughening agent, antioxidant and light absorber. The addition of additives improves the weather resistance of the material to a certain extent. However, it still faces the problems of insufficient notched impact strength and poor flame retardant performance.

[0007] Patent CN202210051553.4 reports an anti-stick and oil-resistant ABS alloy material, its preparation method and uses. By using an anti-stick agent and nano-montmorillonite, a lubricating layer is formed on the ABS alloy material during heating and melting welding, which prevents the carbonization problem of the ABS alloy material caused by long-term adhesion in the hot melt state. However, the introduction of rigid groups into PBT can easily lead to a deterioration in the tensile and impact properties of the material, and a reduction in mechanical properties.

[0008] Patent CN201410186815.3 discloses a heat-resistant ABS resin for spraying and its preparation method. This invention uses a high-flow AS resin and a chemical-resistant modifier to make the heat-resistant ABS have higher flowability and improve the chemical resistance of the material. However, the addition of the heat-resistant agent affects the flowability and toughness of the material, and the gloss of the material will also be affected.

[0009] Existing technologies have reported improving the flame retardancy of ABS resin by directly adding conventional non-bromine flame retardant systems. However, this requires a large amount of these systems, and further addition of flame retardants does not significantly improve the flame retardancy, thus limiting the overall flame retardancy of the material. Furthermore, issues such as poor compatibility or dispersibility of the added flame retardants with the matrix system, and the reduction of gloss by flame retardants, lead to a sacrifice in the mechanical and appearance properties of the material, limiting its comprehensive applications. Additionally, toughening modification of ABS resin affects its weather resistance; while adding additives can improve weather resistance, it results in some loss of mechanical and flame retardant properties. Further research is needed to explore how to improve the flame retardancy and weather resistance of ABS resin materials while maintaining mechanical properties.

[0010] Therefore, an ABS composite resin for improving product gloss and its preparation method are proposed. Summary of the Invention

[0011] The purpose of this invention is to provide an ABS composite resin with improved product gloss and its preparation method. A copolymer is prepared by using pentadiene, butadiene, styrene, and acrylonitrile, which is then compounded with bulk ABS. An anti-aging agent and a toughening agent are added to obtain the ABS composite resin. Adjusting the ratio of isoprene and butadiene and regulating the latex particle size of the copolymer results in a high-gloss ABS composite resin. By controlling the type and amount of bulk ABS and adjusting the amount of copolymer, the tensile properties of the ABS composite resin are significantly improved. By controlling the type and amount of toughening agent and adjusting the type of modifier in the anti-aging agent, the notched impact strength of the obtained ABS composite resin is 15.6 KJ / m. 2 It has significantly improved impact strength; by using fluorine-based modifiers to modify nano-titanium dioxide to obtain an anti-aging agent, the prepared ABS composite resin has significantly improved aging resistance; by using benzoxazine flame retardants in combination with triphenyl phosphate and adjusting the amount of flame retardant, the resulting ABS composite resin has a limiting oxygen index of 35% and good flame retardancy.

[0012] To achieve the above objectives, the present invention provides the following technical solution:

[0013] The present invention provides a method for preparing ABS composite resin to improve the gloss of products. The ABS composite resin includes 50-100 parts of bulk ABS, 50-100 parts of copolymer, 5-25 parts of toughening agent, 5-20 parts of anti-aging agent, 10-30 parts of flame retardant, and 2 parts of antioxidant.

[0014] The preparation method of the ABS composite resin includes the following steps:

[0015] The copolymer, the bulk ABS, the flame retardant, the toughening agent, the anti-aging agent, and the antioxidant are added to a vacuum drying oven and dried at 60°C for 2 hours to obtain a dried material. The dried material is then added to a high-speed mixer and stirred at 500 rpm for 30 minutes until uniformly mixed to obtain a mixture. The mixture is then added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain granules. The granules are then vacuum dried at 85°C for 5 hours and injection molded to obtain ABS composite resin.

[0016] The copolymer is obtained by emulsifying isoprene, butadiene, acrylonitrile, and styrene to initiate the reaction, followed by demulsification, separation, centrifugation, and drying.

[0017] The anti-aging agent is prepared by reacting nanoparticles with a modifier under acidic conditions;

[0018] The flame retardant is selected from a mixture of one of benzoxazine derivatives, polyvinyl chloride, polyphenylene ether, and phenolic resin with triphenyl phosphate; the ratio of the flame retardant used is 1-4:1-4.

[0019] The amount of isoprene used is 20-80 parts, and the amount of butadiene used is 20-80 parts.

[0020] Preferably, the ABS material used in the bulk method is selected from ABS 8391, ABS 3504, ABS275, and ABS 8434.

[0021] Preferably, the toughening agent is selected from styrene-butadiene rubber, butadiene rubber, styrene-butadiene-styrene block copolymer, ethylene-vinyl acetate copolymer, and chlorinated polyethylene.

[0022] Preferably, the method for preparing the copolymer includes the following steps:

[0023] Deionized water, isoprene, rosin soap solution, and potassium persulfate were added to a high-pressure reactor, and butadiene liquid was added using a feed pump. Nitrogen was used to purge the mixture to obtain a reaction solution. The reaction solution was heated to 65°C and polymerized at 200 rpm for 5 hours to obtain a rubber latex. The rubber latex was added to a reaction vessel, heated to 65°C, and stirred until homogeneous to obtain a reaction raw material. A mixture of styrene and acrylonitrile monomers, tert-dodecyl mercaptan, and cumene hydroperoxide were added to the reaction raw material within 1 hour, and the mixture was kept at this temperature for 2 hours to obtain a reaction system. Cucumene hydroperoxide was added to the reaction system, and the mixture was kept at this temperature for 0.5 hours to obtain an ABS emulsion. The ABS emulsion was demulsified, separated, centrifuged, and vacuum dried at 60°C for 2 hours to obtain the copolymer.

[0024] Preferably, the method for preparing the anti-aging agent includes the following steps:

[0025] The nanoparticles were added to a three-necked flask and dissolved in 100 ml of a mixed solution of ethanol and water (V ethanol:V water = 5:1) to obtain a mixed solution. The mixed solution was adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 min, and the modifier was added. The reaction was stirred and reacted for 6 h in a water bath at 85 °C to obtain a reaction system. The reaction system was cooled to room temperature, centrifuged, and the solid sample was washed three times with anhydrous ethanol. Then, it was vacuum dried at 80 °C for 24 h to obtain the anti-aging agent.

[0026] Preferably, the nanoparticles are selected from one of nano-calcium carbonate, nano-silica, nano-titanium dioxide, and nano-alumina.

[0027] Preferably, the modifier is selected from one of perfluorodecyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and methacryloyloxypropyltrimethoxysilane.

[0028] Preferably, the preparation method of the benzoxazine derivative includes the following steps:

[0029] Aniline, 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene, and paraformaldehyde were stirred and mixed evenly in a beaker at room temperature to obtain a mixture. One-tenth of the mixture was added to a 1000 mL flask, heated to 70°C, and reacted for 10 min to obtain reaction solution one. A second batch of one-tenth of the mixture was added to reaction solution one, and reacted for 10 min to obtain reaction solution two. The remaining mixtures were added sequentially. After all the raw materials were added, the reaction temperature was maintained at 110°C, and the mixture was reacted under reflux for 20 min to obtain a reaction system. The reaction system was heated to 130°C, stirred and refluxed for 30 min to evaporate the water, centrifuged, and dried under vacuum at 80°C for 2 h to obtain benzoxazine derivatives.

[0030] Preferably, the operating parameters of the twin-screw extruder are as follows: screw speed is 250 r / min, feed speed is 40 r / min, and the temperatures of the first to eighth temperature zones are 210℃, 215℃, 220℃, 225℃, 230℃, 230℃, 225℃, and 215℃, respectively, with the die head temperature being 220℃.

[0031] Preferably, the operating parameters of the injection molding machine are as follows: zone 1 to zone 3 temperatures are 215℃, 225℃, and 235℃ respectively; nozzle temperature is 230℃; holding time is 10s; cooling time is 20s; holding pressure is 120MPa; injection temperature is 200℃-240℃; and injection pressure is 40%-60% of the maximum pressure.

[0032] Preferably, the antioxidant is selected from antioxidant 1010.

[0033] Another aspect of the present invention provides an ABS composite resin for improving the gloss of a product. The ABS composite resin comprises the bulk ABS, the copolymer, the toughening agent, the anti-aging agent, the flame retardant, and the antioxidant. The ABS composite resin is prepared by any one of the preparation methods described above. The ABS composite resin has a gloss of 96.2%, a tensile strength of 40 MPa, an elongation at break of 32%, a flexural strength of 70 MPa, and a notched impact strength of 15.6 KJ / m. 2 The ABS composite resin exhibits a 28-day gloss retention rate of 97.5% and a 28-day notched impact strength of 14.6 KJ / m. 2 The limiting oxygen index of the ABS composite resin is 35%.

[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0035] 1. This invention uses isoprene, butadiene, styrene, and acrylonitrile to prepare a copolymer. The copolymer is then compounded with ABS using a bulk method. Anti-aging agents, toughening agents, flame retardants, and antioxidants are added to prepare an ABS composite resin. The gloss of the composite resin is improved by changing the injection temperature and injection pressure. Since the scattering of light decreases with increasing rubber particle size within a reasonable range, the gloss of the resin decreases. By adjusting the ratio of isoprene to butadiene, the particle size of the copolymer is changed, and the resulting ABS composite resin achieves a gloss of 96.2%, demonstrating a significant improvement in gloss.

[0036] 2. This invention uses bulk ABS and copolymers in combination. Because bulk ABS has good heat resistance, less residual monomer, and good thermal stability, and the larger rubber particle size can maintain a high elongation at break, the elongation at break of the ABS composite resin is improved by using ABS of different particle sizes in combination. By controlling the type and amount of bulk ABS and adjusting the amount of copolymer, the tensile strength of the ABS composite resin obtained is 40 MPa and the elongation at break is 32%, which has significantly improved tensile properties.

[0037] 3. This invention enhances the impact strength of ABS composite materials by using toughening agents. Under external force, the toughening agent can induce crazes and shear bands in the ABS composite resin. The generation and development of crazes and shear bands consume a large amount of energy, thereby improving the toughness of the ABS composite material. By controlling the type and amount of toughening agent, and simultaneously adjusting the type of modifier in the anti-aging agent, the compatibility between the anti-aging agent and the composite resin is enhanced, synergistically improving the notched impact strength. The resulting ABS composite resin has a flexural strength of 70 MPa and a notched impact strength of 15.6 KJ / m. 2 It has significantly improved impact strength.

[0038] 4. This invention adjusts the types of nanoparticles in the anti-aging agent, utilizing the excellent ultraviolet light shielding properties of nano-titanium dioxide to resist some high-energy ultraviolet radiation and reduce the degree of photoaging damage to ABS resin. Combined with fluorine modifiers, it enhances the compatibility between the anti-aging agent and the composite resin, while simultaneously improving anti-aging capabilities. The resulting ABS composite resin exhibits a 28-day gloss retention rate of 97.5% and a 28-day notched impact strength of 14.6 KJ / m. 2 It has significantly improved resistance to aging.

[0039] 5. This invention utilizes a combination of benzoxazine flame retardants and triphenyl phosphate. During the ring-opening curing of BOZ, a cross-linked network is formed, thereby inhibiting the volatilization of TPP. The phenolic hydroxyl groups formed during curing undergo an esterification reaction with the phosphoric acid and polymetaphosphoric acid generated from the decomposition of TPP at high temperatures, increasing the cross-linking density of the benzoxazine resin and forming a dense char layer on the surface of the burning material, thus achieving a better flame retardant effect. By adjusting the amount of flame retardant, the limiting oxygen index of the obtained ABS composite resin is 35%, which has significantly improved flame retardant performance. Attached Figure Description

[0040] Figure 1 This is a graph showing the effect of injection molding temperature on gloss.

[0041] Figure 2 This is a graph showing the effect of injection pressure on gloss.

[0042] Figure 3 This is a graph showing the change in notched impact strength during accelerated aging experiments in some embodiments of Example 50. Detailed Implementation

[0043] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0045] The ABS 8391, ABS 3504, ABS 8434, and ABS275 described in this invention are ABS produced by bulk method and purchased from Sinopec Shanghai Gaoqiao Petrochemical Co., Ltd.

[0046] The SBS described in this invention is a styrene-butadiene-styrene block copolymer.

[0047] The EVA described in this invention is an ethylene-vinyl acetate copolymer.

[0048] The CPE mentioned in this invention is chlorinated polyethylene.

[0049] The KH-550 described in this invention is 3-aminopropyltriethoxysilane, CAS: 919-30-2.

[0050] The KH-560 described in this invention is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, CAS: 2530-83-8.

[0051] The KH-570 described in this invention is methacryloyloxypropyltrimethoxysilane, CAS: 2530-85-0.

[0052] The BOZ described in this invention is a benzoxazine derivative.

[0053] The TPP mentioned in this invention is triphenyl phosphate, CAS: 115-86-6, purchased from Anhui Zesheng Technology Co., Ltd.

[0054] The PVC used in this invention is polyvinyl chloride, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0055] The PPO mentioned in this invention is polyphenylene ether, which was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0056] The PFR described in this invention is a phenolic resin, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0057] Please see Figures 1 to 3 This invention provides an ABS composite resin for improving product gloss and its preparation method. The technical solution is as follows:

[0058] Example 1

[0059] 100 parts deionized water, 50 parts isoprene, 30 parts rosin soap solution, and 20 parts potassium persulfate were added to a high-pressure reactor. 50 parts butadiene liquid was added using a feed pump, and the mixture was purged with nitrogen to obtain a reaction solution. The reaction solution was heated to 65°C and polymerized at 200 rpm for 5 hours to obtain a rubber latex. 250 parts of the rubber latex were added to a reactor, heated to 65°C, and stirred until homogeneous to obtain a reaction raw material. Using a starvation feeding method, 300 parts of styrene and 100 parts of acrylonitrile monomers, 10 parts of tert-dodecyl mercaptan, and 8 parts of cumene hydroperoxide were added to the reaction raw material within 1 hour, and the mixture was kept at this temperature for 2 hours to obtain a reaction system. 2 parts of cumene hydroperoxide were added to the reaction system, and the mixture was kept at this temperature for 0.5 hours to obtain an ABS emulsion. The ABS emulsion was demulsified, separated by centrifugation, and vacuum dried at 60°C for 2 hours to obtain a copolymer.

[0060] 60 parts of the copolymer, 190 parts of ABS 839, 20 parts of triphenyl phosphate, 15 parts of styrene-butadiene-styrene block copolymer, 10 parts of anti-aging agent, and 2 parts of antioxidant 1010 were placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dried material. The dried material was then added to a high-speed mixer and stirred at 500 r / min for 30 minutes to obtain a mixture. The mixture was then added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain granules. The granules were then vacuum dried at 85°C for 5 hours and injection molded to obtain ABS composite resin.

[0061] Examples 2-14 follow the same preparation method and parameters as Example 1, with differences shown in Table 1.

[0062] Table 1. Variations in component dosage in Examples 1-14

[0063]

[0064]

[0065] Comparative Example 1 follows the same preparation method and parameters as Example 1, except that isoprene is not added.

[0066] Comparative Example 2 follows the same preparation method and parameters as Example 1, except that butadiene is not added.

[0067] Example 15 Gloss Test

[0068] Rubber latex particle size: Place the rubber latex in a sampling bottle and dilute it with distilled water; then place the sampling bottle in the sample cell and measure the particle size of the rubber latex when the temperature reaches 23℃.

[0069] Injection-molded samples of the ABS composite resins prepared in Examples 1-14 and Comparative Examples 1-2 were selected. A 100mm × 90mm × 3mm sample plate was used, and the gloss was measured using a gloss meter (VG7000, purchased from Denshoku, Japan) at a 60° angle. The test results are shown in Table 2. The effect of injection temperature on gloss is as follows: Figure 1 As shown, the effect of injection pressure on gloss is as follows: Figure 2 As shown.

[0070] Table 2 Gloss tests of Examples 1-14 and Comparative Examples 1-2

[0071] Example 1 90.8 307.2 96.2 Example 2 94.8 325.4 95.6 Example 3 93.5 316.2 94.2 Example 4 92.4 314.6 94.8 Example 5 90.8 307.2 96.2 Example 6 85.8 308.5 95.8 Example 7 80.5 310.2 95.1 Example 8 78.2 318.5 92.4 Example 9 90.8 307.2 91.4 Example 10 90.8 307.2 93.6 Example 11 90.8 307.2 94.2 Example 12 90.8 307.2 91.5 Example 13 90.8 307.2 95.2 Example 14 90.8 307.2 94.3 Comparative Example 1 94.5 328.8 90.5 Comparative Example 2 62.2 354.5 55.8

[0072] As shown in Table 1, the rubber latex prepared in Comparative Example 1 without isoprene had a high conversion rate, large latex particle size, and low gloss. In Comparative Example 2 without butadiene, the rubber latex had a low conversion rate, larger particle size, and significantly reduced gloss, possibly due to the higher amount of coagulated material after grafting the pure isoprene latex, leading to a significant decrease in the gloss of the ABS resin. Comparing the results of Examples 1-8, it can be seen that the final conversion rate of the rubber latex decreased significantly with increasing isoprene content in the comonomer, due to the large difference in the reactivity ratio (r) between butadiene and isoprene. Butadiene monomers readily self-polymerize due to their r > 1; isoprene monomers readily polymerize with butadiene due to their r < 1. When the styrene to isoprene feed ratio is changed, a higher isoprene content results in insufficient butadiene for copolymerization in the later stages of the reaction. Reducing the isoprene content leads to less cross-linking, as butadiene is more prone to cross-linking compared to isoprene, resulting in larger emulsion particle sizes. Within a reasonable rubber phase particle size range, increased rubber particle size weakens light scattering and decreases resin gloss. Examples 1, 9-11, and... Figure 1 The results show that as the injection molding temperature increases, the gloss initially increases and then decreases. This is because the increased injection molding temperature reduces the resin viscosity, which facilitates resin flow and molding, thus improving the resin's gloss. However, when the temperature is too high, the high-speed shearing generated during the injection molding process causes frictional heat in the ABS resin melt, leading to excessively high internal resin temperature and resin decomposition. The decomposition gases hinder the contact between the resin and the mold, causing the surface of the part to become hazy, resulting in a continuous decrease in gloss. Comparative studies with Examples 1, 12-14, and... Figure 2 The results show that with the increase of injection pressure, the gloss initially increases and then decreases. Increased injection pressure facilitates the compaction of the molten resin, resulting in closer contact between the resin and the mold surface, thus improving the gloss of the part. However, excessively high injection pressure causes difficulties in demolding, and the material surface suffers external force damage during demolding, reducing the gloss of the part. (See Table 2 and...) Figure 1 , Figure 2 The results show that by using 50 parts of isoprene and 50 parts of butadiene, and controlling the injection pressure and temperature, the gloss of the ABS composite resin obtained is 96.2%, which is a significant improvement in gloss.

[0073] Examples 16-24 follow the same preparation method and parameters as Example 5, with differences shown in Table 3.

[0074] Comparative Example 3 follows the same preparation method and parameters as Example 5, except that bulk ABS is not added.

[0075] Example 25 Tensile property test

[0076] The tensile strength and elongation at break of the ABS composite resins prepared in Examples 16-24 and Comparative Example 3 were tested using a universal testing machine (H10K-S type, Hohenfeld GmbH, Germany).

[0077] Tensile strength: Tested according to ISO527-2-2012, with a tensile speed of 50 mm / min;

[0078] Elongation at break: Tested according to ISO527-2-2012, with a tensile speed of 10 mm / min. The results are shown in Table 3.

[0079] Table 3 Tensile property tests of Examples 16-24 and Comparative Example 3

[0080]

[0081]

[0082] Table 3 shows that the ABS resin used in Comparative Example 3 without bulk ABS exhibits excellent tensile strength but low elongation at break. This is because bulk ABS has better heat resistance, fewer residual monomers, better thermal stability, and larger rubber particle size, generally around 0.5–5 μm, resulting in stronger intermolecular forces. Examples 16-19 show that with the addition of bulk ABS, the tensile strength of the composite resin decreases slightly compared to Comparative Example 3, but the elongation at break increases significantly. With increasing bulk ABS rubber particle size, the tensile strength of the resin remains almost unchanged, while the elongation at break initially decreases and then increases. This is because smaller particle sizes result in weaker intermolecular hydrogen bonding and lower intermolecular forces, preventing the absorption of more energy during stretching. Larger particle sizes weaken light scattering, reducing the resin's gloss. Comparing the results of Examples 16 and 20-24, it can be seen that with the addition of bulk ABS… With increasing ABS dosage, the tensile strength of the composite resin increases slowly and the change is not significant. The elongation at break, however, shows a trend of first increasing and then decreasing with increasing dosage. Because emulsion ABS has better gloss and smaller rubber particle size (generally 0.1–0.7 μm), blending two resins with different rubber particle sizes can improve the elongation at break of the ABS composite resin with minimal impact on tensile strength. Simultaneously, when the bulk ABS dosage is too high, the small-particle-size emulsion ABS is prone to getting trapped in resin cracks, preventing the development of streaks and reducing impact resistance. High elongation at break ABS exhibits significant deformation before fracture, and the fracture surface shows extensional deformation, consuming more energy and enhancing the material's impact resistance. Under heavy loads, it first absorbs energy through plastic deformation. If the energy is completely absorbed, the material will not crack. When the energy exceeds the material's absorption capacity, cracking occurs. The results in Table 3 show that by using ABS 8391 in combination with copolymer and controlling the proportions of bulk ABS and copolymer, the resulting ABS composite resin has a tensile strength of 40 MPa and an elongation at break of 32%, demonstrating significantly improved tensile properties.

[0083] Example 26

[0084] Twenty parts of the nano-calcium carbonate were added to a three-necked flask and dissolved in 100 ml of a mixed solution of ethanol and water (V alcohol:V water = 5:1) to obtain a mixed solution. The mixed solution was adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 min, and five parts of modifier were added. The mixture was stirred and reacted in a water bath at 85 °C for 6 h to obtain a reaction system. The reaction system was cooled to room temperature, centrifuged, and the solid sample was washed three times with anhydrous ethanol. Then, it was vacuum dried at 80 °C for 24 h to obtain the anti-aging agent.

[0085] Preparation of copolymers: prepared according to the preparation method and parameters of Example 5;

[0086] 60 parts of the copolymer, 190 parts of ABS 839, 20 parts of triphenyl phosphate, 10 parts of toughening agent, 10 parts of anti-aging agent, and 2 parts of antioxidant 1010 were placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dried material. The dried material was then added to a high-speed mixer and stirred at 500 r / min for 30 minutes to obtain a mixture. The mixture was then added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain granules. The granules were then vacuum dried at 85°C for 5 hours and injection molded to obtain ABS composite resin.

[0087] Examples 27-37 follow the same preparation method and parameters as Example 26, with differences shown in Table 4.

[0088] Comparative Example 4 follows the same preparation method and parameters as Example 26, except that no modifier is added.

[0089] Comparative Example 5 follows the same preparation method and parameters as Example 26, except that no toughening agent is added.

[0090] Example 38 Impact Strength Test

[0091] The ABS composite resins prepared in Examples 26-37 and Comparative Examples 4-5 were tested for flexural strength using a universal testing machine (H10K-S type, Hohenfeld GmbH, Germany) and for notched impact strength using a cantilever beam impact testing machine (Shenzhen Sansi Zongheng Technology Co., Ltd.).

[0092] Bending strength: Tested according to ISO 178 standard, at a test speed of 5 mm / min;

[0093] Notched impact strength: Tested according to ISO 179-1 standard at a test temperature of 25℃. The test results are shown in Table 4.

[0094] Table 4 Impact strength tests of Examples 26-37 and Comparative Examples 4-5

[0095]

[0096] The results in Table 4 show that the ABS composite resin prepared in Comparative Example 5 without toughening agent has a higher flexural strength, but its notched impact strength is significantly lower than that of Examples 26-37. In Comparative Example 4, without the addition of a modifier to treat the anti-aging agent, the flexural strength and notched impact strength of the resulting composite resin are significantly lower than those of the examples. The addition of the polar silane coupling agent leads to poor compatibility between the ABS composite resin and nano-calcium carbonate, weakening intermolecular forces and preventing the maintenance of high mechanical strength. The results of Examples 26-30 show that the type of toughening agent affects the flexural strength and notched impact strength of the composite resin. Under external force, the toughening agent... The toughening agent can induce crazes and shear bands in ABS composite resin. The generation and development of crazes and shear bands consume a large amount of energy, which improves the toughness of the ABS composite material. However, compared with rubber-based toughening agents, EVA is a flexible polymer with very low impact strength. The weak mechanical strength of EVA offsets the toughening effect of EVA, resulting in a decrease in the impact strength of the ABS composite material. Comparing the results of Examples 26 and 31-34, it can be seen that as the amount of toughening agent increases, the flexural strength of the ABS composite material gradually decreases. Due to the good softness and elasticity of SBS, the flexibility between ABS resin segments increases, and the flexural strength is improved under external force. At this time, the molecular chains are easy to extend, and the chain segments are easy to slip against each other, which leads to a decrease in the flexural strength of the ABS composite. As the toughening agent content increases, the notched impact strength of the composite resin gradually increases. When the dosage exceeds a certain point, the increasing trend of notched impact strength slows down. If the SBS dosage continues to increase, the crazing and shear banding of SBS rubber particles reach saturation, and the toughening effect gradually slows down. At this point, the weaker mechanical properties of SBS dominate. Excessive SBS will reduce the compatibility of the ABS composite resin, resulting in a decrease in impact strength. Comparing the results of Examples 26 and 35-37, it can be seen that using silane coupling agent to modify nano-calcium carbonate produces... The flexural strength of the resulting composite resin remained relatively stable, but the impact strength was significantly increased. Methacryloxypropyltrimethoxysilane, through hydrolysis of siloxane to silanol under acidic conditions, covalently bonds with the hydroxyl groups on the surface of nano-calcium carbonate. The resulting anti-aging agent contains free alkenyl groups, reducing the polarity of nano-calcium carbonate and increasing the compatibility between the anti-aging agent and the composite resin. Simultaneously, it synergistically increases the notched impact strength of the composite resin with the toughening agent. The results in Table 4 show that using 15 parts SBS and modifying nano-calcium carbonate with KH570, the resulting ABS composite resin exhibits a flexural strength of 70 MPa and a notched impact strength of 15.6 KJ / m. 2 It has significantly improved impact strength.

[0097] Examples 39-49 follow the same preparation method and parameters as Example 26, with differences shown in Table 5.

[0098] Table 5. Variations in the dosage of components 39-49 in Examples 5

[0099]

[0100]

[0101] Comparative Example 6 follows the same preparation method and parameters as Example 26, except that no anti-aging agent is added.

[0102] Example 50: Aging Resistance Test

[0103] According to GB / T 16422.2-1999 standard for exposure testing of plastic light sources, an SH60BⅡ type xenon lamp climate test chamber (xenon lamp power 6000W, average irradiance 2000W / m²) was used. 2 Accelerated aging tests simulating natural climate were conducted on the ABS samples prepared in Examples 39-49 and Comparative Example 6. Gloss and notched impact strength were tested at 0d, 7d, 14d, and 28d, respectively. The results are as follows: Figure 3 As shown in Table 6, the results of 28-day gloss retention rate and 0-day and 28-day notched impact strength are recorded.

[0104] Table 6. Aging resistance test results of Examples 39-49 and Comparative Example 6

[0105] Example 39 90.2 15.6 12.8 Example 40 91.5 15.4 12.6 Example 41 96.8 15.5 13.8 Example 42 92.5 15.8 13.2 Example 43 95.6 12.3 10.9 Example 44 94.8 12.6 11.5 Example 45 97.5 15.5 14.6 Example 46 92.8 13.5 11.6 Example 47 94.3 14.2 12.8 Example 48 97.2 13.8 12.9 Example 49 97.5 12.2 11.2 Comparative Example 6 80.6 11.5 6.8

[0106] As shown in Table 6, the gloss retention rate of the ABS composite resin prepared without anti-aging agent in Comparative Example 6 decreased significantly, and the impact strength also decreased significantly. The notched impact strength after 28 days was significantly lower than that of the ABS resin prepared in Examples 39-49. The results of Examples 39-42 show that the change in nanoparticles had almost no effect on the notched impact strength at 0 days, but the gloss retention rate and notched impact strength at 28 days decreased significantly. Because the polybutadiene links in ABS resin contain unsaturated double bonds, they are susceptible to free radical degradation under ultraviolet radiation, producing conjugated double bonds. This leads to yellowing, surface chalking, and decreased gloss in the aging ABS resin, as well as a decline in mechanical properties. Since nano-titanium dioxide has excellent ultraviolet light shielding properties, adding nano-titanium dioxide can resist some high-energy ultraviolet radiation and reduce the degree of photoaging damage to the ABS resin. The results of Examples 39 and 43-45 show that using perfluorosilane couplers... The coupling agent further improves the aging resistance of ABS resin. Because fluorine atoms are introduced into the composite resin molecular chain and exhibit a helical distribution, the low surface energy of fluorine atoms causes them to volatilize and migrate to the resin surface. The shielding effect of fluorine atoms on ultraviolet light further weakens the impact of light on the resin. Results from Examples 39 and 46-49 show that as the amount of anti-aging agent increases, the gloss retention rate of ABS resin gradually increases and tends to remain constant, but the notched impact strength shows a trend of first increasing and then decreasing. This is because the high-filling-content nano-titanium dioxide cannot be well dispersed in the ABS resin, and some nano-titanium dioxide forms agglomerates. These larger agglomerates can cause defects in the ABS composite resin, resulting in stress concentration and reducing the bonding force between the nano-titanium dioxide particles and the ABS resin, thus decreasing the impact strength of the ABS composite resin. However, the impact on aging resistance is relatively small, with little change in notched impact strength at 28 days. (See Table 6 and...) Figure 3 The results showed that the ABS composite resin prepared with 10 parts of anti-aging agent had a gloss retention rate of 97.5% after 28 days and a notched impact strength of 14.6 KJ / m² after 28 days. 2 It has significantly improved resistance to aging.

[0107] Example 51

[0108] Preparation of benzoxazine derivatives:

[0109] A mixture of 3 mol aniline, 3.0 mol 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene (phenolic hydroxyl group), and 6 mol paraformaldehyde was stirred and mixed thoroughly in a beaker at room temperature to obtain a mixed solution. One-tenth of the mixed solution was added to a 1000 mL flask, heated to 70 °C, and reacted for 10 min to obtain reaction solution one. A second batch of 1 / 10 of the mixed solution was added to reaction solution one, and reacted for 10 min to obtain reaction solution two. The remaining mixed solutions were added sequentially. After the raw materials were added, the reaction temperature was maintained at 110 °C, and the reaction was carried out under reflux for 20 min to obtain the reaction system. The reaction system was heated to 130 °C, stirred and refluxed for 30 min to evaporate the water, centrifuged, and dried under vacuum at 80 °C for 2 h to obtain benzoxazine derivatives.

[0110] The ABS composite resin was prepared according to the preparation method and parameters of Example 45.

[0111] Examples 52-62 follow the same preparation method and parameters as Example 45, with differences shown in Table 7.

[0112] Comparative Example 7 follows the same preparation method and parameters as Example 45, except that no benzoxazine flame retardant is added.

[0113] Comparative Example 8 follows the same preparation method and parameters as Example 45, except that triphenyl phosphate is not added.

[0114] Example 63 Flame retardant performance test

[0115] The ABS composite resins prepared in Examples 51-62 and Comparative Examples 7-8 were sampled with a sample size of 150mm × 6.5mm × 3mm. The limiting oxygen index was tested according to GB / T2406-1993, and the test results are shown in Table 7.

[0116] Table 7 Flame retardant performance tests of samples from Examples 51-62 and Comparative Examples 7-8

[0117]

[0118]

[0119] As shown in Table 7, the limiting oxygen index (LOI) of the ABS resins prepared using a single flame retardant in Comparative Examples 7 and 8 was significantly lower than that in Examples 51-62. While BOZ alone exhibited good heat resistance, its low crosslinking density prevented it from achieving the desired flame retardant effect. Since ABS itself is difficult to char, the addition of TPP alone resulted in the lack of a char source, hindering the formation of a char layer to stop combustion. Furthermore, TPP's tendency to volatilize at low temperatures further impacted the flame retardant effect. Comparing the results of Examples 51-58, it is evident that using TPP in combination with other flame retardants effectively improved the flame retardant performance of ABS resin. With increasing BOZ dosage, the LIO index showed a trend of first increasing and then decreasing. Due to BOZ's good charring properties, it could participate in charring and flame retardancy with TPP. The BOZ ring-opening curing process forms a cross-linked network, thereby inhibiting TPP volatilization. Simultaneously, the phenolic hydroxyl groups formed during ring-opening curing react with the phosphoric acid and polymetaphosphoric acid generated from the decomposition of TPP at high temperatures, increasing the cross-linking density of the benzoxazine resin and forming a dense char layer on the surface of the combustible material, thus achieving a better flame retardant effect. Comparing the results of Examples 51 and 59-62, it can be seen that the flame retardant performance of the ABS composite resin gradually increases with the increase of the total amount of flame retardant. However, excessive BOZ leads to reduced compatibility with the system, thereby reducing the mechanical properties of ABS. Based on the results in Table 7, using BOZ / TPP as a flame retardant compound, while controlling the amount and proportion of flame retardant, results in an ABS composite resin with a limiting oxygen index of 35%, exhibiting significantly improved flame retardant performance.

[0120] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing ABS composite resin to improve the gloss of products, characterized in that: The ABS composite resin comprises 50-100 parts of bulk ABS, 50-100 parts of copolymer, 5-25 parts of toughening agent, 5-20 parts of anti-aging agent, 10-30 parts of flame retardant, and 2 parts of antioxidant. The preparation method of the ABS composite resin includes the following steps: The copolymer, the bulk ABS, the flame retardant, the toughening agent, the anti-aging agent, and the antioxidant are added to a vacuum drying oven and dried at 60°C for 2 hours to obtain a dried material. The dried material is then added to a high-speed mixer and stirred at 500 rpm for 30 minutes until uniformly mixed to obtain a mixture. The mixture is then added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain granules. The granules are then vacuum dried at 85°C for 5 hours and injection molded to obtain the ABS composite resin. The copolymer is obtained by emulsifying isoprene, butadiene, acrylonitrile, and styrene to initiate the reaction, followed by demulsification, separation, centrifugation, and drying. The anti-aging agent is prepared by reacting nanoparticles with a modifier under acidic conditions; The flame retardant includes flame retardant one and flame retardant two; flame retardant one is selected from one of benzoxazine derivatives, polyvinyl chloride, polyphenylene ether, and phenolic resin; flame retardant two is selected from triphenyl phosphate; the ratio of flame retardant one to flame retardant two is 1-4:1-4; The amount of isoprene used is 20-80 parts, and the amount of butadiene used is 20-80 parts.

2. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The ABS used in the bulk method is selected from one of ABS 8391, ABS 3504, ABS275, and ABS 8434.

3. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The toughening agent is selected from one of styrene-butadiene rubber, butadiene rubber, styrene-butadiene-styrene block copolymer, ethylene-vinyl acetate copolymer, and chlorinated polyethylene.

4. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The method for preparing the copolymer includes the following steps: Deionized water, isoprene, rosin soap solution, and potassium persulfate were added to a high-pressure reactor. Butadiene liquid was added using a feed pump, and nitrogen was used to purge the mixture to obtain a reaction solution. The reaction solution was heated to 65°C and polymerized at 200 rpm for 5 hours to obtain a rubber latex. The rubber latex was added to a reaction vessel, heated to 65°C, and stirred until homogeneous to obtain a reaction raw material. The styrene and acrylonitrile mixed monomers, tert-dodecyl mercaptan, and cumene hydroperoxide were added to the reaction raw material within 1 hour, and the mixture was kept at this temperature for 2 hours to obtain a reaction system. Cubic hydroperoxide was added to the reaction system, and the mixture was kept at this temperature for 0.5 hours to obtain an ABS emulsion. The ABS emulsion was demulsified, separated, centrifuged, and vacuum dried at 60°C for 2 hours to obtain the copolymer.

5. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The method for preparing the anti-aging agent includes the following steps: The nanoparticles were added to a three-necked flask, and 100 ml of a mixed solution of ethanol and water (V ethanol:V water = 5:1) was added to dissolve them and obtain a mixed solution. The mixed solution was adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 min, and the modifier was added. The mixture was stirred and reacted in a water bath at 85 °C for 6 h to obtain a reaction system. The reaction system was cooled to room temperature, centrifuged, and the solid sample was washed three times with anhydrous ethanol. Then, it was vacuum dried at 80 °C for 24 h to obtain the anti-aging agent.

6. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The nanoparticles are selected from one of nano-calcium carbonate, nano-silica, nano-titanium dioxide, and nano-alumina.

7. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The modifier is selected from one of perfluorodecyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and methacryloyloxypropyltrimethoxysilane.

8. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The preparation method of the benzoxazine derivative includes the following steps: Aniline, 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene, and paraformaldehyde were stirred and mixed evenly in a beaker at room temperature to obtain a mixed solution. One-tenth of the mixed solution was added to a 1000 mL flask, heated to 70°C, and reacted for 10 min to obtain reaction solution one. A second batch of one-tenth of the mixed solution was added to reaction solution one, and reacted for 10 min to obtain reaction solution two. The remaining mixed solutions were added sequentially. After the raw materials were added, the reaction temperature was maintained at 110°C, and the reaction was carried out under reflux for 20 min to obtain the reaction system. The reaction system was heated to 130°C, stirred and refluxed for 30 min to evaporate the water, centrifuged, and dried under vacuum at 80°C for 2 h to obtain the benzoxazine derivative.

9. The method for preparing an ABS composite resin for improving product gloss according to claim 1, characterized in that: The injection temperature of the injection molding machine is 200℃-240℃, and the injection pressure is 40%-60% of the maximum pressure; the antioxidant is selected from antioxidant 1010.

10. An ABS composite resin for improving the gloss of products, characterized in that: The ABS composite resin comprises the bulk ABS, the copolymer, the toughening agent, the anti-aging agent, the flame retardant, and the antioxidant; the ABS composite resin is prepared by the preparation method according to any one of claims 1-9; the ABS composite resin has a gloss of 96.2%; the ABS composite resin has a tensile strength of 40 MPa and an elongation at break of 32%; the ABS composite resin has a flexural strength of 70 MPa and a notched impact strength of 15.6 KJ / m. 2 The ABS composite resin exhibits a 28-day gloss retention rate of 97.5% and a 28-day notched impact strength of 14.6 KJ / m. 2 The limiting oxygen index of the ABS composite resin is 35%.

Citation Information

Patent Citations

  • Halogen-free flame retardant and heat resistant ABS (acrylonitrile butadiene styrene copolymers) plastic for automotive interior trim parts and preparation method thereof

    CN103923433A

  • Heat-resistant ABS resin for spraying and preparation method thereof

    CN104004312A

  • PC-ABS (polycarbonate and acrylonitrile-butadiene-styrene) composite material with high filling property, high anti-impact property and high weather-resistant property and preparation method thereof

    CN106832846A

  • A kind of anti-stick oil-resistant ABS alloy material and its preparation method and use

    CN114292488B